Inhibition of Calcineurin and Glycogen Synthase Kinase‐3β by Ricinoleic Acid Derived from Castor Oil. Issue 2 (22nd December 2019) - Yoshida, Jun; Okawa, Yusuke; Oyama, Takuya; Shimoda, Nozomu; Uesugi, Shota; Takagi, Hiroshi; Ito, Yoshiaki; Kimura, Ken‐ichi
Abstract: Ricinoleic acid (RA) is the main fatty acid component of castor oil and was found to inhibit Ca 2+ ‐signal transduction pathway‐mediated cell cycle regulation in a yeast‐based drug screening assay. RA is expected to have antidiabetic, antiallergy, and/or anticancer properties but its target molecule is unknown. To identify a novel pharmacological effect of RA, we investigated its target molecule in the Ca 2+ ‐signal transduction pathway. RA inhibition of calcineurin (CN) was examined in a yeast‐based CN inhibitor screening assay using the rsp5 A401E mutant and in a phosphatase assay using recombinant human CN. RA showed growth‐restoration activity at 5 μg/spot in the CN inhibitor screening assay with the rsp5 A401E yeast strain. Furthermore, it directly inhibited CN without immunophilins at K i = 33.7 μM in a substrate‐competitive manner. The effects of RA on CN in mammalian cells were further evaluated by measuring β‐hexosaminidase (β‐HEX) release in RBL‐2H3 cells. RA at 50 μM suppressed the release of β‐HEX from RBL‐2H3 cells. Moreover, this compound was found to inhibit glycogen synthase kinase‐3β (GSK‐3β), as determined by a kinase assay using recombinant human GSK‐3β. RA inhibited GSK‐3β at K i = 1.43 μM in a peptide substrate‐competitive manner. The inhibition of GSK‐3β by this molecule was further assessed in mammalian cells by measuring the inhibition of glucose production in H4IIE rat hepatoma cells. RA at 25 μM suppressed glucose production in these cells. These findings indicate that RA and/or castor oil could be a useful functional fatty acid to treat allergy or type 2 diabetes.